The Influence of 'Big Brothers : ' How Important are Regional Factors for Uruguay? - Sosa, Sebastian (IMF Working Papers; Working Paper, 2010)
This paper examines the role played by regional factors in Uruguay, identifies the sources and transmission mechanisms of shocks stemming from the region, and assesses how vulnerable Uruguay is to a potential crisis in the region. Using a VAR model with block exogeneity restrictions, it finds that shocks from Argentina-which account for about 20 percent of Uruguayan output fluctuations-have large and rapid effects. This is mainly due to the existence of idiosyncratic real and financial linkages between Uruguay and Argentina, which also explain the very high correlation between their business cycles. The analysis of previous crises in the region suggests that despite the importance of these strong linkages, and despite the fact the two deepest crises in recent Uruguayan history followed crises in Argentina, Uruguay is now clearly less vulnerable to financial contagion from the region.